The advertisement call of Centrolene notostictum (Anura, Centrolenidae) with a new record of geographic distribution in Tolima, Colombia - Viuche-Lozano, Andres; Enciso-Calle, Maria Paula; Bernal, Manuel Hernando (Zootaxa, 2018)
Centrolene notostictum Ruiz-Carranza & Lynch,1991 is a glassfrog known from the Cordillera Oriental of Colombia—in the Departments of Boyacá, Cundinamarca, Norte de Santander and Santander (Frost 2017)—and the Venezuelan versant of the Sierra de Perijá (Rojas et al. 2012) from 1600 to 2440 masl. Although males have been found calling on the upper surface of the leaves of ferns and Heliconeaceae on the margins of a small fast-flowing stream (Rojas et al. 2012), no quantitative description of the advertisement call of C. notostictum is currently available. During fieldwork in the Galilea Natural Forest (on the western slope of Cordillera Oriental in the municipality of Villarrica, department of Tolima, Colombia) in 2016 and 2017, we found three vocalizing males of C. notostictum. Herein, we report the first geographic record of this species for the department of Tolima and describe its previously unknown advertisement call.